Synthesis, Trafficking, and Localization of Muscarinic Acetylcholine Receptors - Nathanson, Neil M. (2008)
Muscarinic acetylcholine receptors are members of the G-protein coupled receptor superfamily that are expressed in and regulate the function of neurons, cardiac and smooth muscle, glands, and many other cell types and tissues. The correct trafficking of membrane proteins to the cell surface and their subsequent localization at appropriate sites in polarized cells are required for normal cellular signaling and physiological responses. This review will summarize work on the synthesis and trafficking of muscarinic receptors to the plasma membrane and their localization at the cell surface.